Influence of hysteresis loop shape on the nonlinear dynamics of shape memory alloy oscillator excited by non-ideal energy sources - Piccirillo, V.; Tusset, A. M.; Balthazar, J. M. [UNESP]; Bernardini, D.; Rega, G. (AIP Publishing, 2014)
The dynamical response of systems with shape memory alloy (SMA) presents a different behavior due to their nonlinear characteristic. SMA nonlinear response is associated with adaptive dissipation related to their hysteretic behavior. This paper discusses the nonlinear responses of shape-memory non-ideal oscillators, based on a thermomechanical consistent model with four state variables. Two cases are investigating, namely, the case when SMA presents a large hysteresis loop and another one with less hysteresis. Computer simulations are carried out via a numerical approach showing qualitative results concerned with regular and non-regular motions.
Keywords: non-ideal system; Nonlinear dynamics; shape memory material; thermomechanical coupling